(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Communication skill is critical in today employment world since most employers look for candidates to fill different positions that involves communication skills. With regard to verbal and non-verbal communication and in addition to the symbolic exchange of information, a crucial part of work and private life. This research will focus on the effectiveness of the courses in communication skills on employment of the graduate students. This is because it emphasises on the importance of these courses by pointing out how they help the students during placement interviews, through enhancing skills like presentation, writing, listening and interpersonal communication skills.